IDENTIFIKASI KEMAMPUAN PENYESUAIAN SOSIAL (SOCIAL ADJUSMENT) SISWA DI KELAS IV SEKOLAH DASAR NEGERI SEGUGUS 3 KECAMATAN TERARA - Alfina Fibria; Darmiany; Muhammad Sobri; Siti Istiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the social adjustment ability of students in class IV cluster 3 Terara sub-district. The results of this study are expected to be useful for students, teachers and other researchers. This study is descriptive with quantitative methods. The subjects in this study were all students in class IV cluster 3 Terara sub-district totaling 176 students. Data collection techniques using questionnaires, documentation and interviews. Data analysis using descriptive analysis techniques. Based on the results of data analysis, the social adjustment ability that is categorized as very high is 69 students with a percentage of 58%. The social adjustment ability that is categorized as high is 45 studen -ts with a percentage of 38% and the social adjustment ability that is categorized as sufficient is 4 students with a percentage of 4%. Thus, according to the calculation of the average value, it can be concluded that the social adjustment ability of students in class IV cluster 3 is categorized as high 80. The results of this study are expected that students will be more serious in paying attention to their social adjustment and teachers will provide guidance to students so that their social adjustment ability does not become low. The factors that influence social adjustment skills are: 1) parenting patterns, 2) school environment, 3) student appearance, 4) student self-confidence, 5) student ability to adjust.